Pneumonia in mice produced by Neisseria gonorrhoeae. Issue 1 (February 1977) - Johnson, A P; Taylor-Robinson, D; Slavin, G
Abstract : Gonococci of colony type 1 were introduced by intranasal inoculation into the lungs of mice in an attempt to produce infection. The organisms were eliminated from the three strains of mice used within 24 hours of challenge. Cyclophosphamide treatment of mice failed to render them susceptible although the organisms disappeared more slowly. The lungs of immunologically normal animals that had received either viable or heat-killed gonococci were acutely inflamed with infiltration of bronchioles and alveoli by polymorphonuclear and mononuclear leucocytes. Most of the changes had resolved after about four days. In cyclophosphamide-treated mice pulmonary infiltration by polymorphonuclear leucocytes was not evident, suggesting that these cells were not primarily responsible for the clearance of the gonococci. Despite the failure to produce a sustained infection, this model may be valuable for studying the local inflammatory effect of gonococcal endotoxin.